I think it'd be better if you gave us some sort of diagram with it?
Answer:
It increases
Step-by-step explanation:
PLZZ mark brainliest!!!
Answer:
I have no idea
Step-by-step explanation:
Answer:
![\left(ab^2x-b^4a^3\right)^2:\quad a^2b^4x^2-2a^4b^6x+a^6b^8](https://tex.z-dn.net/?f=%5Cleft%28ab%5E2x-b%5E4a%5E3%5Cright%29%5E2%3A%5Cquad%20a%5E2b%5E4x%5E2-2a%5E4b%5E6x%2Ba%5E6b%5E8)
Step-by-step explanation:
Given the expression
![\left(ab^2\:x\:-b^4a^3\right)^2](https://tex.z-dn.net/?f=%5Cleft%28ab%5E2%5C%3Ax%5C%3A-b%5E4a%5E3%5Cright%29%5E2)
solving the expression
![\left(ab^2\:x\:-b^4a^3\right)^2](https://tex.z-dn.net/?f=%5Cleft%28ab%5E2%5C%3Ax%5C%3A-b%5E4a%5E3%5Cright%29%5E2)
![\mathrm{Apply\:Perfect\:Square\:Formula}:\quad \left(a-b\right)^2=a^2-2ab+b^2](https://tex.z-dn.net/?f=%5Cmathrm%7BApply%5C%3APerfect%5C%3ASquare%5C%3AFormula%7D%3A%5Cquad%20%5Cleft%28a-b%5Cright%29%5E2%3Da%5E2-2ab%2Bb%5E2)
![a=ab^2x,\:\:b=b^4a^3](https://tex.z-dn.net/?f=a%3Dab%5E2x%2C%5C%3A%5C%3Ab%3Db%5E4a%5E3)
so the expression becomes
![=\left(ab^2x\right)^2-2ab^2xb^4a^3+\left(b^4a^3\right)^2](https://tex.z-dn.net/?f=%3D%5Cleft%28ab%5E2x%5Cright%29%5E2-2ab%5E2xb%5E4a%5E3%2B%5Cleft%28b%5E4a%5E3%5Cright%29%5E2)
![=a^2b^4x^2-2a^4b^6x+a^6b^8](https://tex.z-dn.net/?f=%3Da%5E2b%5E4x%5E2-2a%5E4b%5E6x%2Ba%5E6b%5E8)
Thus,
![\left(ab^2x-b^4a^3\right)^2:\quad a^2b^4x^2-2a^4b^6x+a^6b^8](https://tex.z-dn.net/?f=%5Cleft%28ab%5E2x-b%5E4a%5E3%5Cright%29%5E2%3A%5Cquad%20a%5E2b%5E4x%5E2-2a%5E4b%5E6x%2Ba%5E6b%5E8)